THE APPLICATION OF ISLAMIC ECONOMIC SECURITY SYSTEM FOR A BETTER HUMAN SECURITY IN INDONESIA - Dewi, Gemala (UI Scholars Hub, 2013)
As the 2010 Indonesian demographic Statistic data predicted that in the year 2020-2030 Indonesia will have overpopulation of young people at the productive age (18-50 years old) in about 69%. So there is a need to find solution on jobs and welfare for those segments of people. Islam as the religion of majority people of Indonesia has a teaching regarding this matter that has been known as Islamic economic security system, by means of zakat, waqf, trading and business manner that could give some solutions for the betterment for human economic security to this country. By using normative and comparative method of research, this paper will lead to the conclusion that the country needs to lagislate the shariah principles of contract and economic system due to secure the human rights on transactions and economic activities.